Dynamic adsorption of cationic surfactants at the alkane/water interface - Salamah, Abdulsalam Hassan Ahmed (Curtin University, 2015)
The adsorption of surfactants at oil/water has numerous practical applications in industrial processes. In this study, the dynamic adsorption at the oil/water interface was investigated in the two systems: (i) CTAB at both hexane and decane interfaces, and (ii) a Gemini surfactant, C14C3C14 at decane/water interface. A new modelling approach was developed and effectively models the adsorption. The results indicated the strong influence of oil phase on the surfactant adsorption.